1987
DOI: 10.1002/pc.750080305
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reinforced melt processible polymer composites: Extrusion, compression, and injection molding

Abstract: Rheological properties, extrusion, fiber spinning, compression, and injection molding of blends of polycarbonate and two thermotropic liquid crystal polymers based on wholly aromatic copolyesters have been studied. Blends were prepared using an internal Banbury mixer and static Koch mixer. Based upon differential scanning calorimetry and dynamic mechanical measurements, these blends have been shown to be incompatible in the entire range of concentrations. During extrusion and injection molding at high strain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(89 citation statements)
references
References 23 publications
8
79
2
Order By: Relevance
“…These results indicate the effectiveness of the reinforcing action of the liquidcrystalline polymer, mainly due to the fibrillar morphology obtained during mixing, as already reported in the literature [19][20][21]. No significant role seems to be played by PKFE, probably ascribable to the low extent of interchain reactions between the components, which result in an insufficiently improved adhesion.…”
Section: Mechanical Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…These results indicate the effectiveness of the reinforcing action of the liquidcrystalline polymer, mainly due to the fibrillar morphology obtained during mixing, as already reported in the literature [19][20][21]. No significant role seems to be played by PKFE, probably ascribable to the low extent of interchain reactions between the components, which result in an insufficiently improved adhesion.…”
Section: Mechanical Propertiessupporting
confidence: 82%
“…Additionally, to obtain fibrils of large aspect ratio, a proper concentration of TLCP is compelled together with a proper value of the viscosity ratio between TLCP and thermoplastics [8,9,14,17,18]. Excellent mechanical properties have been achieved for blends of thermoplastics and LCPs when partial miscibility exists and, in some cases, also when they are not miscible or compatible [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…After primary and secondary differentiation of ! ),.FP with respect to r and l, the curved energy surface is found to have a barrier with a saddle point at r* and l*, which are given by r* =2a.//),.f l* =4a.//),.f (2) and ! ),.FP * =nr* 2 l*!…”
Section: Explanation Of Morphology Based On Crystallization Kinetics mentioning
confidence: 96%
“…Kiss 1 suggested a concept of"in situ composite," emphasizing the fact that the TLCP reinforcement could be formed "in situ" during processing. Isayev et al 2 called them as "self-reinforced melt processable polymer composite". According to Brostow et al 3 the composite could be classified into two kinds: one was the traditional fiber-reinforced composite, being classified as a heterogenous composite; the other was the molecular composite, such as selfreinforced plastics and the molecular composite in the strict meaning suggested by Takayanagi.…”
mentioning
confidence: 99%
“…The morphology and the resultant properties of the blends are highly dependent on the processing conditions and the composition of the blend components. Moreover, it has been reported that the viscosity ratio and the strain rate are also the important parameters governing the fibrillation of TLCP in the blend (24)- (27) . Generally, the fibrillation of TLCP is enhanced as the viscosity ratio of TLCP to polymer matrix becomes mostly less than unity (28)- (29) and it has also been reported that the elongational flow causes more extensive fibrillation than the shear flow (30)- (32) .…”
Section: Introductionmentioning
confidence: 99%